PEMANFAATAN LIMBAH KULIT BAWANG MERAH UNTUK PESTISIDA NABATI SEBAGAI ALTERNATIF PESTISIDA SINTETIS - Herlambang, Tedy; Sulistiyowati, Retno; Suyani, Ida Sugeng; Hidayatullah, M. Rizky; Yuliawati, Hela; Shodiqy, Fika Anjani; Sa’adatun N., Dwi; Fauziyah, Ghina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
This community service aims to utilize shallot peel waste as a basic ingredient for biopesticides. The background of this service is concern about the dominant use of synthetic pesticides by farmers as a strategy for controlling pests and diseases. This strategy is unsustainable in the long term because of its deadly side effects and reactions not only for humans and other animals, but also for non-target plants, organisms around the plants and the environment. In addition, there are also concerns about the development of pest resistance to this synthetic pesticide. The target is farmers in Klaseman Village, Gending District, Probolinggo Regency by utilizing abundant available shallot peeled waste in their sorrounding. The main activities that covers counseling, demonstration of the making process, demonstration of application on plants and witnessing the effectiveness of the application provide positive results in the form of increased knowledge, skills about the benefits of shallot peel waste. Based on the effectiveness of the application of onion peel extract as a vegetable pesticide can inhibit the growth of onion plant pests, it is hoped that in the long term the community will reduce the use of synthetic pesticides and switch to plant-based pesticides. Keywords: biopesticide, shallot peel waste